Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1071/ah010057
|View full text |Cite
|
Sign up to set email alerts
|

Empirical comparison of DRG variants using cardiovascular surgery data: initial results of a project at 18 German hospitals

Abstract: In 2000, the responsibility for selecting a DRG variant for use in Germany was assigned to a body comprising representatives of hospitals and insurers called the Self-Administration Board (or Board in this paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…Further severity markers identified in the current research might also be included in future regression specification, for example, brochiectasis and cardiomyopathy for lung and heart transplant related services, respectively.We turn now to the implications of the research for casemix classification and funding developments in Germany. [42].…”
Section: Risk-adjusted Specified Grant Calculationsmentioning
confidence: 95%
See 3 more Smart Citations
“…Further severity markers identified in the current research might also be included in future regression specification, for example, brochiectasis and cardiomyopathy for lung and heart transplant related services, respectively.We turn now to the implications of the research for casemix classification and funding developments in Germany. [42].…”
Section: Risk-adjusted Specified Grant Calculationsmentioning
confidence: 95%
“…Those particularly relevant to the current research concern the adequacy of the classification system including co-morbidities,complications,expensive and/or modern procedures,sensitivity to extreme cases and their relative size, cost homogeneity of the residual group,resistance of the system to gaming and cost homogeneity. An excellent detailed comparison of the underlying theories and constructions of the eight variants are provided by Rochell and Roeder [41] and Roeder et al [42]. They found that the French GHM-DRG and Australian AR-DRG variants had the best medical logic.The Australian system was outstanding regarding its explanation of its design and operation, and its statistical performance in resource use homogeneity.…”
Section: Developments In Germanymentioning
confidence: 98%
See 2 more Smart Citations
“…Third, the documentation, as well as the “grouper” had already been translated (Leber, Schlottmann and von Stakkelberg, 2001). On the other hand, AR‐DRGs had performed better with respect to cost homogeneity and medical logic in a comparative evaluation of 18 German hospitals (Roeder et al., 2001). Moreover, the Australian government was prepared to make its grouper available for modification and enhancement, while the commercial AP‐DRGs could only be licensed.…”
Section: Cross‐national Policy Learning In Germany Switzerland and mentioning
confidence: 99%